PENGARUH SHIFT KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT MAJU TAMBAK SUMUR DESA GENTING JUAR - Jeta Herlosti; Khairul Bahrun (UM. Bengkulu, 2026)
This study aims to determine whether work shifts and the work environment significantly influence employee performance at PT Maju Tambak Sumur, Genting Juar Village, both partially and simultaneously. This study employed quantitative research. The population comprised all employees at PT Maju Tambak Sumur, Genting Juar Village. Simple random sampling was used for sampling. Fifty-seven respondents were selected, and data were collected through questionnaires and analyzed using multiple linear regression analysis. The results of the study show that work shifts have a positive effect on the performance of employees of PT Maju Tambak Sumur, Genting Juar village, with the results of the t-test count> t-table (10,754> 2,004), then the work environment has a positive effect on the performance of employees of PT Maju Tambak Sumur, Genting Juar village, with the results of the t-test count> t-table (3,726> 2,004), then the results of the study show that work shifts and work environment have a positive and significant influence partially or simultaneously on employee performance with the results of the F-test count> F-table (91,552> 3,16). Keywords: Work shifts, work environment, employee performance